2010
DOI: 10.1007/s00415-010-5822-y
|View full text |Cite
|
Sign up to set email alerts
|

Lateral trunk flexion in Parkinson’s disease: EMG features disclose two different underlying pathophysiological mechanisms

Abstract: Pisa Syndrome is clinically defined as the sustained lateral bending of the trunk worsened by a prolonged sitting position or by walking. Pisa syndrome, also termed lateral trunk flexion (LTF), has been rarely reported in patients affected by Parkinson's disease (PD) and, therefore, the pathophysiology has been poorly investigated. In some cases, the hyperactivity of paravertebral muscles contralateral to the leaning side has been interpreted as a sign of dystonia; however, it is well known that paravertebral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
69
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(76 citation statements)
references
References 29 publications
4
69
0
3
Order By: Relevance
“…Electromyographic (EMG) recording of paraspinal muscles failed to show any pattern of denervation or myopathy, 36,72,73 except in 2 of 26 patients in one study. 7 Very few imaging studies have been performed on the paraspinal muscles.…”
Section: A S T R I O T O E T a Lmentioning
confidence: 99%
See 2 more Smart Citations
“…Electromyographic (EMG) recording of paraspinal muscles failed to show any pattern of denervation or myopathy, 36,72,73 except in 2 of 26 patients in one study. 7 Very few imaging studies have been performed on the paraspinal muscles.…”
Section: A S T R I O T O E T a Lmentioning
confidence: 99%
“…An early study using lumbar computed tomography scan showed atrophy of the lumbar paraspinal muscles with fatty degeneration, which was more pronounced on the side affected by deviation. 72 More recently, a magnetic resonance imaging study showed bilateral paraspinal lumbar muscle atrophy that was unrelated to the side affected by the deviation, and more pronounced in hypoactive muscles as shown by EMG recordings. 73 Although these data are difficult to interpret, they do not support the notion that musculoskeltal mechanisms play a primary role in Pisa syndrome.…”
Section: A S T R I O T O E T a Lmentioning
confidence: 99%
See 1 more Smart Citation
“…1a). The patient underwent conventional EMG recordings in the paravertebral muscles at the thoracic-lumbar level T12-L1 (longissimus thoracis muscle) [2]. Recordings, that were performed with the patient in stance position and during voluntary right and left lateral trunk flexion, showed a pattern of a co-contraction of agonist and antagonist muscles compatible with dystonia of paraspinal muscles (Fig.…”
mentioning
confidence: 99%
“…33,34 Most of the clinical studies have also shown that patients lean away from the most affected side, which is consistent with animal studies. [35][36][37] However, few investigators failed to replicate this finding. 28,30,31 Another observation pointing to the involvement of central dopaminergic system is that PS can occur as a motor complication of PD.…”
Section: Pathophysiologymentioning
confidence: 99%